Subthreshold Micropulse Laser Modulates Retinal Neuroinflammatory Biomarkers in Diabetic Macular Edema - Frizziero, Luisa (J Clin Med, 2021)
Subthreshold micropulse laser treatment has become a recognized option in the therapeutic approach to diabetic macular edema. However, some yet undefined elements pertaining to its mechanism of action and most effective treatment method still limit its clinical diffusion. We reviewed the current literature on subthreshold micropulse laser treatment, particularly focusing on its effects on the modulation of retinal neuroinflammation. Subthreshold micropulse laser treatment seems to determine a long-term normalization of specific retinal neuroinflammatory metabolic pathways, contributing to the restoration of retinal homeostasis and the curtailing of local inflammatory processes. Optimized and standardized parameters ensure effective and safe treatment.